Should we pay attention to the place where the coronary artery bypass is grafted to the left anterior descending artery? - Wasilewski, Jarosław; Peryt-Stawiarska, Sylwia; Przybylski, Roman; Głowacki, Jan; Zembala, Marian (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2012)
Despite the fact that the risk factors are systemic in nature, arterial lesions are restricted to the points which are typically areas of disturbed flow and low and oscillatory shear stress. The evidence that haemodynamics plays a key role in atheroma formation is a non-random plaque distribution. Preferred locations are the outer lateral wall of the bifurcation, and areas near to the side branches. Atherosclerotic plaques are eccentric, and in segments where the vessel has no side branches they emerge from the inner curvature. Vulnerable and ruptured plaques tend to cluster in the proximal portion of the left anterior descending artery (LAD). Grafts to the LAD are typically placed in the distal part of the vessel. The effect of graft placement on abnormal flow patterns and shear stress in the arterial segment proximal to the anastomosis site is discussed, in relation to accelerated progression of atherosclerotic disease of the grafted artery.